Women in Managerial Positions in Greek Education - Anastasia Athanassoula-Reppa; Manolis Koutouzis (Arizona State University, 2002)
This article deals with the under-representation of women in managerial positions in Greece. While substantial progress has been made in terms of the legal framework that ensures equal rights to both men and women in the country, evidence shows that there are barriers that inhibit women from pursuing and taking such positions, resulting to covert discrimination. This occurs despite the dominance of women in Greek education. We regard that kind of discrimination as a democratic deficit; it contradicts the notion of "democratic citizenship." Although we do not advocate a quota system, we stand for implementation of basic democratic principles, which could prevent such discrimination.